An analysis of citations of IRRI scholars' doctoral dissertations, 1991-2000 - Manlangit, Rene B.; Faderon, Rosalie B.; Quiros, Edgardo B.; Tarlit, Rodolfo Y. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
The purpose of this study was to investigate the pattern of citations in IRRI scholars' doctoral dissertations submitted to the University of the Philippines Los Baños for the period 1991-2000 by using citation analysis as the methodology to determine the characteristics of the materials cited by IRRI scholars.
There are 80 out of 104 (76.92) total of IRRI scholars' Type II dissertations for these 10-year periods as sample population and a total of 11,544 citations were recorded. A minimum of five dissertations sample per major were required to maintain the reliability and validity of the study result. The majors with enough sample population are: Agronomy with 17 sample dissertations; Soil science with 15 sample dissertations; Plant breeding with 13 sample dissertations; Agricultural economics with 11 sample dissertations; Plant pathology with 7 sample dissertations; Entomology and Genetics with 6 sample dissertations each; and Botany with 5 sample dissertations. Journals were the most heavily cited type of IRRI library material accounting for 67.30 (7,774) of all citations. Theses and dissertations accounted for 2.69 (311) while "Others" (general grouping for books, book chapter, proceedings, etc.) accounted for 30.01 (3,459). Only the format for recording serial or journal citations is consistent from other earlier citation studies. Journal bibliographic format percentages per eight (8) major shows that five majors results are above the overall 67.30 journal citation rate. Journal citation rate of 83.44 was noted for Genetics; 72.89 for Plant Pathology; 71.34 percent for Plant Breeding; 69.93 for Botany; and 69.22 for Soil Science. The three (3) majors which fall below the overall journal citation rate, are Agronomy with 64.27; entomology, with 63.38; and Agricultural Economics, with 52.29. There are 993 journal titles identified in this study with one journal title (Science), used/cited in eight majors (8:8 ratio); 20 titles used/cited in seven majors;16 titles used/cited in six majors; 26 titles in five majors; 52 titles in 4 majors; 72 titles in three majors; 165 titles in two majors; and 642 titles used/cited in at least one majors.
This study shows that there are journal titles in the most frequently cited journal titles that are not agricultural in nature but are included as the literature of interest to rice science researcher validating earlier claims of agriculture as an interdisciplinary field as per Adimorah's definition. Lastly, the result of the study clearly validates Trueswell 80/20 pattern for journal use, 80 of the citations could be satisfied by only 20 of the cited journal titles.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Bibliographic citations; Dissertations, Academic -- Philippines; Scholars -- Philippines